LITERACY AND SECONDARY ORALITY: (SEBUAH ANALISIS PERBANDINGAN KISAH ROMANTIS â€œA WALK TO REMEMBERâ€ VERSI NOVEL DAN FILM) - Triwardani, Reny; Wicandra, Obed Bima (Institute of Research and Community Outreach - Petra Christian University, 2008)
Electronic media has given birth to public life based on oral culture, though different from the previous understanding, in this case cited as the secondary oral form. The second difference is oral form can be said that the oral culture of the first (primary orality) is based on human physical, whereas the secondary orality is based on technology. It can be seen that the development of communication technology, especially electronic media resource uses audio as an important tool in communication and delivery of information. The forms of media in secondary orality are radio, television, movies, and other electronic media. This paper provides exposure to a comparison between written culture that manifests itself in a novel with a secondary orality embodied in a film. Both types of cultures used to study the novel and film of the same title, namely